Effects of genetic and non-genetic factors on growth traits of high yielding dairy seed calves and genetic parameter estimates - Rahman, Syed Mohammad Ashiqur; Bhuiyan, Mohammad Shamsul Alam; Bhuiyan, Abul Kashem Fazlul Haque (Journal of Advanced Veterinary and Animal Research, 2015)
The study was conducted to know the effects of several genetic and non-genetic factors like season, sex, year of birth, genotype of calves and milk yield of dam associated with growth performance of crossbred calves. Data were collected from registered farmers during the period of May, 2011 to April, 2013. Birth weight, three-month weight, six-month weight, weaning weight and heritability estimates of those growth performances were performed using a total of 82 registered calves which had pedigree information having the genotypes of 25% Local - 75% Friesian and 37.5% Local - 62.5% Friesian. The average birth, three- month, six-month and weaning weight of calves were 29.33, 64.32, 99.06 and 151.77 kg, respectively. The effects of non-genetic factors like sex, season of birth and genotype were non-significant (P>0.05) for the traits birth weight, three-month, six-month, weaning weight and average daily gain of calves. However, year of birth was found significant on birth (P<0.01), three-month and six-month (P<0.05) weight; but non- significant (P>0.05) on weaning weight and average daily gain of calves. The heritability estimates were 0.40±0.09, 0.46±0.08, 0.39±0.12 and 0.50±0.12 for the traits birth weight, three-month weight, six-month weight and weaning weight, respectively. Estimated heritabilities of live weights suggest that individual own performance basis selection would be more effective for increasing growth and therefore, should be paid more emphasis in cattle improvement program. http://dx.doi.org/10.5455/javar.2015.b116